Interpreting undergraduate research posters in the literature classroom - Manarin, Karen (Teaching and Learning Inquiry, 2016)
This essay explores the use of undergraduate research posters in English literature classrooms; at the same time, it argues for a scholarship of teaching and learning responsive to how meaning is constructed in the arts and humanities. Our scholarly practice requires interaction with texts and with each other, yet the undergraduate research paper typically does not involve much interaction between peers. The posters disseminate preliminary interpretations of research projects to peers; they are a way to make visible some of the cognitive, affective, and aesthetic aspects of literary research. This essay analyzes student reflections on both the process of creating and the process of presenting research posters before providing “close readings” of several posters. Reading the posters reveals key elements of students’ interactions with literary texts: close reading, integration, negotiation, theoretical generalization, and aesthetic judgment. As the students explored a less familiar genre, disciplinary processes of knowledge creation were defamiliarized and made visible.